حقوق نسواں کی عصری تحریکیں اور ان کے مقاصد کا ناقدانہ جائزہ: A Critical Analysis of Contemporary Feminist Movements and their Objectives - Malik, Hafiza Bushra; Dr. Ahmad; Alazhari, Dr. Zahoor Ullah (Al-Irfan, 2023)
The Progressive Feminists think that all human are equal, the up and down of classes is harmful for Humanity, and Women cannot enjoy freedom in the Capitalism. End of exploiter and oppressions against women, their equal rights as humans, equal chances for education and to make ideology in Philosophy are the main objectives of World Feminist Movements. To perform their duties and gain the rights as the teaching s of Islam are the objectives of faithful women in Muslims. There are also many types of Feminist Movements in Pakistan. Some movements have the objectives of women’s empowerment through politics and legislations. These movements are struggling for women’s equal rights in the society. Most of them want Secularism to ensure their objectives. The implement of Islamic teachings is the objective of such women who have the Islamic background. Muslim women should be aware that the objectives of the Western Feminist Movement are leading to Antichrist. To obey the West is the loss of this life and the next life after death, as it is foretold by the Prophet Muhammad (PBUH). It is a narrative research about the worldwide Feminist movements and in Pakistan and about their objectives. The objectives of contemporary Feminist movements are analyzed and criticized in this article.